High-strength low-warpage 3D printing nylon modified material and preparation method thereof
By adding modified silicon carbide whiskers, modified carbon fibers and hyperbranched polymers to 3D printed nylon materials, and using a segmented cooling process, the problem of warping and deformation of nylon materials during 3D printing is solved, improving the problem of nylon materials being warped and deformed during 3D printing, The strength and accuracy of the material meet the requirements of industrial applications.
Patent Information
- Application Number
- CN202411323369.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-13
AI Technical Summary
During the 3D printing process, nylon materials are prone to warping and deformation due to their crystallization characteristics and thermal expansion coefficient, which is difficult to meet the requirements of industrial applications for the accuracy and application temperature of 3D printed products.
Using high-strength, low-warping 3D printing nylon modified materials and preparation methods, it is grafted by adding modified silicon carbide whiskers, modified carbon fibers, hyperbranched polymers containing benzene rings, crystallization accelerators and maleic anhydride grafting The components such as agents and other components are adopted, and the segmented cooling process is adopted to improve the tensile strength, flexural strength and fluidity of the material, and reduce deformation and warping.
It significantly improves the uniformity and mechanical properties of the material, reduces internal stress during cooling, reduces warping and deformation, and meets the accuracy and temperature requirements of 3D printed products in industrial applications.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of 3D printing, and in particular relates to a high-strength and low-warping 3D printing nylon modified material and a preparation method thereof. Background Art
[0002] 3D printing (3DP) is a technology that uses digital model files as the basis and uses bondable materials such as powdered metal or plastic to construct objects by printing layer by layer. It has the characteristics of fast molding speed, high processing precision, high material utilization rate, and easy operation.
[0003] Fused deposition modeling (FDM) is one of the most widely used 3D printing processes. It heats and melts thermoplastic wire (printing material) in the print head and extrude it through a micro nozzle. The molten wire moves three-dimensionally on the printing platform according to the cross-sectional profile information given by the computer, and is selectively deposited on the workbench, rapidly cooled and solidified, and bonded layer by layer to form a three-dimensional solid structure. In the process of fused deposition modeling, printing materials are the key factors affecting process development and finished product performance.
[0004] Common printing materials include polylactic acid (PLA), acrylonitrile-butadiene-styrene copolymer (ABS), polycarbonate polyester (PC), polyethylene terephthalate-1,4-cyclohexanedimethanol (PETG), nylon (PA), etc. Among them, nylon has good mechanical properties, but due to its crystallization characteristics and thermal expansion coefficient, it is easy to warp and deform during the 3D printing process, which cannot meet the requirements of industrial applications for the accuracy and application temperature of 3D printed products. Summary of the invention
[0005] The purpose of the present invention is to provide a high-strength and low-warping 3D printing nylon modified material, which not only improves the tensile strength and bending strength of the material, but also reduces the deformation and warping of the material.
[0006] The technical solution adopted by the present invention to solve the above problems is: a high-strength and low-warping 3D printing nylon modified material and a preparation method thereof, which comprises the following raw materials in parts by weight: Nylon resin 64-87 parts 1-2 parts of crystallization accelerator Maleic anhydride graft toughening agent 1-2 parts 1-2 parts of hyperbranched polymer containing benzene ring Modified silicon carbide whiskers 5-15 parts Modified carbon fiber 5-15 parts Lubricating dispersant TAF 0.2-0.5 parts Wherein, the modified silicon carbide whisker is obtained by coating a layer of conductive polymer on the surface of the silicon carbide whisker and then performing electrochemical treatment; The modified carbon fiber is obtained by coating a layer of layered dihydroxy compound on the surface of the carbon fiber and then introducing functionalized substances between the dihydroxy compound layers through ion exchange.
[0007] Preferably, the hyperbranched polymer containing benzene rings is at least one of hyperbranched polystyrene, hyperbranched polyaryletherketone, and hyperbranched polyarylethersulfone. Among them, hyperbranched polystyrene is polymerized by free radicals, and the benzene ring structure provides rigidity and thermal stability, and its branched structure reduces intermolecular entanglement and improves fluidity; the presence of benzene rings and ketone groups in hyperbranched polyaryletherketone gives it excellent chemical and thermal stability, and the branched structure helps to improve the melt index; the benzene rings and sulfone groups in hyperbranched polyarylethersulfone provide rigidity and chemical stability, and the branched structure helps to improve the melt index.
[0008] Preferably, the crystallization accelerator is a compound of an organic phosphate and a benzoic acid derivative.
[0009] More preferably, the organic phosphate is diphenyl phosphate DPP and its derivatives, and the benzoic acid derivative is terephthalic acid PTA and its esters.
[0010] Preferably, the maleic anhydride grafted toughening agent is at least one of maleic anhydride grafted polyethylene MAH-g-PE, maleic anhydride grafted polypropylene MAH-g-PP, maleic anhydride grafted polystyrene MAH-g-PS, maleic anhydride grafted polyethylene-vinyl alcohol copolymer MAH-g-EVOH, and maleic anhydride grafted thermoplastic elastomer MAH-g-TPE.
[0011] Preferably, the conductive polymer is polyaniline.
[0012] Preferably, the layered dihydroxy compound is Mg-Al LDH, and the functionalized substance is a fluorine-containing polymer.
[0013] Another object of the present invention is to provide a method for preparing a high-strength and low-warpage 3D printed nylon modified material, comprising the following steps: (1) Drying the nylon resin: (2) adding the nylon resin, crystallization accelerator, maleic anhydride graft toughening agent, benzene ring-containing hyperbranched polymer, modified silicon carbide whisker, and modified carbon fiber obtained in step (1) into a high-speed mixer and mixing them evenly to obtain a mixture; (3) melt-blending, extruding and granulating the mixture obtained in step (2) using a twin-screw extruder to obtain granules; (4) The pellets obtained in step (3) are sent to a vacuum oven for drying, and then extruded through a single screw extruder, and then cooled in sections to obtain a 3D printing nylon modified material, wherein the 3D printing nylon modified material is a 3D printing wire with a diameter of 1.75 mm to 3 mm.
[0014] Preferably, the processing temperature of the twin-screw extruder in step (3) is 250-290°C.
[0015] Preferably, the processing temperature of the single screw extruder in step (4) is 250-290°C, and the cooling temperatures used in the segmented cooling process are set to 240°C, 220°C, 200°C, 180°C, 160°C, 100°C, and 40°C, respectively.
[0016] Compared with the prior art, the advantages of the present invention are: (1) The present invention adds modified silicon carbide whiskers, coats a layer of conductive polymer on the surface of the silicon carbide whiskers, and then performs electrochemical treatment to make the surface charged. The electroactive coating greatly improves the dispersibility of the silicon carbide whiskers in the nylon resin and avoids agglomeration, while enhancing the interface bonding and improving the uniformity and mechanical properties of the material.
[0017] (2) The present invention adds modified carbon fiber, which is coated with a layer of layered dihydroxy compound on the surface of the carbon fiber, and then introduces functionalized substances (fluoropolymers) between the dihydroxy compound layers through ion exchange. The LDH coating can significantly enhance the interfacial bonding force between the carbon fiber and the nylon matrix, thereby improving the tensile strength and flexural strength of the material.
[0018] (3) In the preparation method of the present invention, a segmented cooling process is adopted after the nylon modified material is formed. The segmented cooling process can significantly reduce the internal stress generated during the cooling process, thereby reducing the deformation and warping of the material; in particular, it is first slowly cooled in a higher temperature section and then quickly cooled in a lower temperature section.
[0019] (4) The addition of a hyperbranched polymer containing benzene rings in the present invention can improve the melt index of the material, that is, the fluidity of the material, avoid material degradation caused by high shear rates during processing, and ensure the stability of the flow.
[0020] (5) The addition of a crystallization accelerator in the present invention can not only stabilize the crystallization rate of the nylon material and shorten the material cooling time, but also improve the fluidity of the nylon material during 3D printing, without the need to add other lubricants and release agents.
[0021] (6) The present invention adds a maleic anhydride graft toughening agent to increase the viscosity of the nylon material during 3D printing, thereby improving the printing quality.
[0022] (7) The present invention adds a lubricating dispersant TAF, which has a low addition amount and excellent dispersibility. It not only increases the surface brightness of the nylon modified material and improves processing fluidity, but also can reduce the processing temperature by 3 to 5°C and reduce the torque of the screw, thereby reducing machine wear and increasing the service life of the machine. DETAILED DESCRIPTION
[0023] The present invention is further described in detail below with reference to the embodiments. Example 1
[0024] A high-strength, low-warping 3D printing nylon modified material and a preparation method thereof, comprising the following raw materials in parts by weight: 70 parts of nylon PA6 resin 1 part of crystallization accelerator Maleic anhydride grafted polyethylene 1 part Hyperbranched polystyrene 1 part Modified silicon carbide whiskers 8 parts Modified carbon fiber 8 parts Lubricating dispersant TAF 0.3 parts The crystallization accelerator is a compound of diphenyl phosphate DPP and terephthalic acid PTA in a mass ratio of 1:1.
[0025] The modified silicon carbide whiskers are prepared by the following preparation method: (1) Dissolve 0.4 g of sodium dodecylbenzene sulfonate (dispersant) in 400 ml of 0.2 mol / L hydrochloric acid solution, then add 1 g of silicon carbide whisker, stir at high speed for 10 min at room temperature, stir at low speed for 20 min, then add 1 g of aniline hydrochloric acid, continue stirring to mix evenly, then drop 50 ml of ammonium persulfate hydrochloric acid solution (dissolve 1.75 g of ammonium persulfate in 50 ml of dilute hydrochloric acid solution), control the dropping time for 10 min, continue stirring for 4 hours, filter, and repeatedly wash with anhydrous ethanol until the filtrate is clear, then repeatedly wash with 0.06 mol / L hydrochloric acid solution for 3 times, and finally dry in a vacuum drying oven at 60°C for 24 hours to obtain silicon carbide whiskers coated with polyaniline.
[0026] (2) Assembling the three-electrode system: Working electrode: Silicon carbide whiskers coated with polyaniline are evenly spread on conductive glass or conductive carbon paper as working electrodes.
[0027] Reference electrode: Use a standard silver chloride electrode (Ag / AgCl).
[0028] Counter electrode: Use a platinum electrode.
[0029] The three-electrode system was placed in an electrolytic cell containing an electrolyte (1 M hydrochloric acid solution) and connected to an electrochemical workstation for electrochemical cyclic voltammetry (V test, with the potential range set to -0.2 V to 0.8 V, a scan rate of 50 mV / s, and 5 cycles. This process allowed polyaniline to undergo redox reactions and adjust its conductivity and surface charge. After the electrochemical treatment, the sample was removed from the electrolyte, washed with deionized water to remove the residual electrolyte, and finally dried in an oven at 50 °C for 2 h to obtain modified silicon carbide whiskers.
[0030] The modified carbon fiber is prepared by the following preparation method: (1) Clean the surface of the carbon fiber with acetone to remove impurities and oil stains, then immerse the carbon fiber in concentrated nitric acid to oxidize the surface to increase hydrophilicity and surface active sites. After treatment, wash it thoroughly with deionized water and dry it.
[0031] (2) Prepare LDH precursor solution: Dissolve 2.0 g magnesium nitrate and 1.0 g aluminum nitrate in 100 ml deionized water, stir evenly, slowly add 1 M NaOH solution until the pH value reaches 10, and continue stirring to form a precipitate: (3) The pretreated carbon fiber is placed in an LDH precursor solution and reacted at 70° for 24 hours. After the reaction is completed, it is washed with deionized water several times until the pH value is 7, and the carbon fiber containing the LDH coating is filtered and collected with filter paper.
[0032] (4) The LDH-coated carbon fiber was immersed in a 0.01 M polytetrafluoroethylene solution (polytetrafluoroethylene was dissolved in chlorine trifluoride and stirred at 180°C for 24 hours), and reacted at 50°C for 12 hours. After the reaction, the treated carbon fiber was washed with deionized water to remove the unreacted polytetrafluoroethylene, and finally dried at 80°C for 2 hours to obtain the modified carbon fiber.
[0033] A method for preparing a high-strength and low-warpage 3D printing nylon modified material comprises the following steps: (1) Drying the nylon resin at 100°C for 3 hours; (2) adding the nylon resin, crystallization accelerator, maleic anhydride graft toughening agent, benzene ring-containing hyperbranched polymer, modified silicon carbide whisker, and modified carbon fiber obtained in step (1) into a high-speed mixer and mixing them evenly to obtain a mixture; (3) melt-blending, extruding and granulating the mixture obtained in step (2) using a twin-screw extruder to obtain granules, wherein the operating parameters of the melt extrusion process are: extrusion temperature of 280° C., die head temperature of 280° C., and main engine speed of 200 rpm; (4) The pellets obtained in step (3) are sent to a vacuum oven and dried at 100°C for 4 hours, and then extruded by a single screw extruder, and then cooled in sections to obtain a 3D printing nylon modified material, wherein the 3D printing nylon modified material is a 3D printing wire with a diameter of 1.75 mm, wherein the working parameters of the melt extrusion process are: extrusion temperature of 280°C, head temperature of 280°C, main engine speed of 200 rpm, and the cooling temperatures used in the section cooling process are set to 240°C, 220°C, 200°C, 180°C, 160°C, 100°C, and 40°C, respectively. Example 2
[0034] A high-strength, low-warping 3D printing nylon modified material and a preparation method thereof, comprising the following raw materials in parts by weight: 85 parts of nylon PA6 resin 2 parts of crystallization accelerator Maleic anhydride grafted polypropylene 2 parts Hyperbranched polyaryletherketone 2 parts Modified silicon carbide whisker 15 parts Modified carbon fiber 15 parts Lubricating dispersant TAF 0.5 parts The crystallization accelerator is a compound of diphenyl phosphate DPP and terephthalic acid PTA in a mass ratio of 1:1.
[0035] The modified silicon carbide whiskers are prepared by the following preparation method: (1) Dissolve 0.4 g of sodium dodecylbenzene sulfonate (dispersant) in 400 ml of 0.2 mol / L hydrochloric acid solution, then add 1 g of silicon carbide whisker, stir at high speed for 10 min at room temperature, stir at low speed for 20 min, then add 1 g of aniline hydrochloric acid, continue stirring to mix evenly, then drop 50 ml of ammonium persulfate hydrochloric acid solution (dissolve 1.75 g of ammonium persulfate in 50 ml of dilute hydrochloric acid solution), control the dropping time for 10 min, continue stirring for 4 hours, filter, and repeatedly wash with anhydrous ethanol until the filtrate is clear, then repeatedly wash with 0.06 mol / L hydrochloric acid solution for 3 times, and finally dry in a vacuum drying oven at 60°C for 24 hours to obtain silicon carbide whiskers coated with polyaniline.
[0036] (2) Assembling the three-electrode system: Working electrode: Silicon carbide whiskers coated with polyaniline are evenly spread on conductive glass or conductive carbon paper as working electrodes.
[0037] Reference electrode: Use a standard silver chloride electrode (Ag / AgCl).
[0038] Counter electrode: Use a platinum electrode.
[0039] The three-electrode system was placed in an electrolytic cell containing an electrolyte (1 M hydrochloric acid solution) and connected to an electrochemical workstation for electrochemical cyclic voltammetry (V test, with the potential range set to -0.2 V to 0.8 V, a scan rate of 50 mV / s, and 5 cycles. This process allowed polyaniline to undergo redox reactions and adjust its conductivity and surface charge. After the electrochemical treatment, the sample was removed from the electrolyte, washed with deionized water to remove the residual electrolyte, and finally dried in an oven at 50 °C for 2 h to obtain modified silicon carbide whiskers.
[0040] The modified carbon fiber is prepared by the following preparation method: (1) Clean the surface of the carbon fiber with acetone to remove impurities and oil stains, then immerse the carbon fiber in concentrated nitric acid to oxidize the surface to increase hydrophilicity and surface active sites. After treatment, wash it thoroughly with deionized water and dry it.
[0041] (2) Prepare LDH precursor solution: Dissolve 2.0 g magnesium nitrate and 1.0 g aluminum nitrate in 100 ml deionized water, stir evenly, slowly add 1 M NaOH solution until the pH value reaches 10, and continue stirring to form a precipitate: (3) The pretreated carbon fiber is placed in an LDH precursor solution and reacted at 70° for 24 hours. After the reaction is completed, it is washed with deionized water several times until the pH value is 7, and the carbon fiber containing the LDH coating is filtered and collected with filter paper.
[0042] (4) The LDH-coated carbon fiber was immersed in a 0.01 M polytetrafluoroethylene solution (polytetrafluoroethylene was dissolved in chlorine trifluoride and stirred at 180°C for 24 hours), and reacted at 50°C for 12 hours. After the reaction, the treated carbon fiber was washed with deionized water to remove the unreacted polytetrafluoroethylene, and finally dried at 80°C for 2 hours to obtain the modified carbon fiber.
[0043] A method for preparing a high-strength and low-warpage 3D printing nylon modified material comprises the following steps: (1) Drying the nylon resin at 100°C for 3 hours; (2) adding the nylon resin, crystallization accelerator, maleic anhydride graft toughening agent, benzene ring-containing hyperbranched polymer, modified silicon carbide whisker, and modified carbon fiber obtained in step (1) into a high-speed mixer and mixing them evenly to obtain a mixture; (3) melt-blending, extruding and granulating the mixture obtained in step (2) using a twin-screw extruder to obtain granules, wherein the operating parameters of the melt extrusion process are: extrusion temperature of 280° C., die head temperature of 280° C., and main engine speed of 200 rpm; (4) The pellets obtained in step (3) are sent to a vacuum oven and dried at 100°C for 4 hours, and then extruded by a single screw extruder, and then cooled in sections to obtain a 3D printing nylon modified material, wherein the 3D printing nylon modified material is a 3D printing wire with a diameter of 1.75 mm, wherein the working parameters of the melt extrusion process are: extrusion temperature of 280°C, head temperature of 280°C, main engine speed of 200 rpm, and the cooling temperatures used in the section cooling process are set to 240°C, 220°C, 200°C, 180°C, 160°C, 100°C, and 40°C, respectively. Example 3
[0044] A high-strength, low-warping 3D printing nylon modified material and a preparation method thereof, comprising the following raw materials in parts by weight: 80 parts of nylon PA6 resin 1.5 parts of crystallization accelerator Maleic anhydride grafted polystyrene 1.5 parts Hyperbranched polystyrene 2 parts Modified silicon carbide whisker 10 parts Modified carbon fiber 10 parts Lubricating dispersant TAF 0.4 parts The crystallization accelerator is a compound of diphenyl phosphate DPP and terephthalic acid PTA in a mass ratio of 1:1.
[0045] The modified silicon carbide whiskers are prepared by the following preparation method: (1) Dissolve 0.4 g of sodium dodecylbenzene sulfonate (dispersant) in 400 ml of 0.2 mol / L hydrochloric acid solution, then add 1 g of silicon carbide whisker, stir at high speed for 10 min at room temperature, stir at low speed for 20 min, then add 1 g of aniline hydrochloric acid, continue stirring to mix evenly, then drop 50 ml of ammonium persulfate hydrochloric acid solution (dissolve 1.75 g of ammonium persulfate in 50 ml of dilute hydrochloric acid solution), control the dropping time for 10 min, continue stirring for 4 hours, filter, and repeatedly wash with anhydrous ethanol until the filtrate is clear, then repeatedly wash with 0.06 mol / L hydrochloric acid solution for 3 times, and finally dry in a vacuum drying oven at 60°C for 24 hours to obtain silicon carbide whiskers coated with polyaniline.
[0046] (2) Assembling the three-electrode system: Working electrode: Silicon carbide whiskers coated with polyaniline are evenly spread on conductive glass or conductive carbon paper as working electrodes.
[0047] Reference electrode: Use a standard silver chloride electrode (Ag / AgCl).
[0048] Counter electrode: Use a platinum electrode.
[0049] The three-electrode system was placed in an electrolytic cell containing an electrolyte (1 M hydrochloric acid solution) and connected to an electrochemical workstation for electrochemical cyclic voltammetry (V test, with the potential range set to -0.2 V to 0.8 V, a scan rate of 50 mV / s, and 5 cycles. This process allowed polyaniline to undergo redox reactions and adjust its conductivity and surface charge. After the electrochemical treatment, the sample was removed from the electrolyte, washed with deionized water to remove the residual electrolyte, and finally dried in an oven at 50 °C for 2 h to obtain modified silicon carbide whiskers.
[0050] The modified carbon fiber is prepared by the following preparation method: (1) Clean the surface of the carbon fiber with acetone to remove impurities and oil stains, then immerse the carbon fiber in concentrated nitric acid to oxidize the surface to increase hydrophilicity and surface active sites. After treatment, wash it thoroughly with deionized water and dry it.
[0051] (2) Prepare LDH precursor solution: Dissolve 2.0 g magnesium nitrate and 1.0 g aluminum nitrate in 100 ml deionized water, stir evenly, slowly add 1 M NaOH solution until the pH value reaches 10, and continue stirring to form a precipitate: (3) The pretreated carbon fiber is placed in an LDH precursor solution and reacted at 70° for 24 hours. After the reaction is completed, it is washed with deionized water several times until the pH value is 7, and the carbon fiber containing the LDH coating is filtered and collected with filter paper.
[0052] (4) The LDH-coated carbon fiber was immersed in a 0.01 M polytetrafluoroethylene solution (polytetrafluoroethylene was dissolved in chlorine trifluoride and stirred at 180°C for 24 hours), and reacted at 50°C for 12 hours. After the reaction, the treated carbon fiber was washed with deionized water to remove the unreacted polytetrafluoroethylene, and finally dried at 80°C for 2 hours to obtain the modified carbon fiber.
[0053] A method for preparing a high-strength and low-warpage 3D printing nylon modified material comprises the following steps: (1) Drying the nylon resin at 100°C for 3 hours; (2) adding the nylon resin, crystallization accelerator, maleic anhydride graft toughening agent, benzene ring-containing hyperbranched polymer, modified silicon carbide whisker, and modified carbon fiber obtained in step (1) into a high-speed mixer and mixing them evenly to obtain a mixture; (3) melt-blending, extruding and granulating the mixture obtained in step (2) using a twin-screw extruder to obtain granules, wherein the operating parameters of the melt extrusion process are: extrusion temperature of 280° C., die head temperature of 280° C., and main engine speed of 200 rpm; (4) The pellets obtained in step (3) are sent to a vacuum oven and dried at 100°C for 4 hours, and then extruded by a single screw extruder, and then cooled in sections to obtain a 3D printing nylon modified material, wherein the 3D printing nylon modified material is a 3D printing wire with a diameter of 1.75 mm, wherein the working parameters of the melt extrusion process are: extrusion temperature of 280°C, head temperature of 280°C, main engine speed of 200 rpm, and the cooling temperatures used in the section cooling process are set to 240°C, 220°C, 200°C, 180°C, 160°C, 100°C, and 40°C, respectively.
[0054] Comparative Example 1 The only difference from Example 1 is that no modified silicon carbide whiskers are added.
[0055] Comparative Example 2 The only difference from Example 1 is that the modified silicon carbide whiskers are replaced with silicon carbide whiskers, that is, unmodified silicon carbide whiskers are added.
[0056] Comparative Example 3 The only difference from Example 1 is that no modified carbon fiber is added.
[0057] Comparative Example 4 The only difference from Example 1 is that the modified carbon fiber is replaced by carbon fiber, that is, unmodified carbon fiber is added.
[0058] Comparative Example 5 The only difference from Example 1 is that no segmented cooling process is adopted, and natural air cooling is adopted.
[0059] The 1.75 mm 3D printing wires prepared in Examples 1-3 and Comparative Examples 1-5 were pelletized and injection molded, and the injection molded specimens were respectively subjected to tensile performance tests (GB / T1040.2-2006), bending strength tests (GB / T1446-2006), and impact performance tests (GB / T1943-2008).
[0060] The warpage test was carried out with reference to Patent 201910239834.0. The 1.75 mm 3D printing wires prepared in Examples 1-3 and Comparative Examples 1-5 were placed in an FDM 3D printer to print a 8×8×3 cm square frame product at a printing temperature of 260°C and a base plate temperature of 90°C. The warpage of the product was tested, specifically as follows: the warpage of the four outer planes of the test product was tested 5 times each, and the average value was taken. Warpage = warpage height / plane diagonal length.
[0061] The test results are shown in Table 1: Table 1 Performance test results of 3D printing wires of Examples 1-3 and Comparative Examples 1-5
[0062] In addition to the above embodiments, the present invention also includes other implementation modes. Any technical solutions formed by equivalent transformation or equivalent replacement should fall within the protection scope of the claims of the present invention.
Claims
1. A high-strength, low-warpage 3D printing nylon modified material and a preparation method thereof, characterized in that: By weight, it includes the following raw materials: Nylon resin 64-87 parts 1-2 parts of crystallization accelerator Maleic anhydride graft toughening agent 1-2 parts 1-2 parts of hyperbranched polymer containing benzene ring Modified silicon carbide whiskers 5-15 parts Modified carbon fiber 5-15 parts Lubricating dispersant TAF 0.2-0.5 parts Wherein, the modified silicon carbide whisker is obtained by coating a layer of conductive polymer on the surface of the silicon carbide whisker and then performing electrochemical treatment; The modified carbon fiber is obtained by coating a layer of layered dihydroxy compound on the surface of the carbon fiber and then introducing functionalized substances between the dihydroxy compound layers through ion exchange.
2. The high-strength, low-warping 3D printing nylon modified material according to claim 1, characterized in that: The hyperbranched polymer containing benzene rings is at least one of hyperbranched polystyrene, hyperbranched polyaryletherketone and hyperbranched polyarylethersulfone.
3. The high-strength and low-warping 3D printing nylon modified material according to claim 1, characterized in that: The crystallization accelerator is a compound of organic phosphate and benzoic acid derivative.
4. The high-strength, low-warpage 3D printing nylon modified material according to claim 3, characterized in that: The organic phosphate is diphenyl phosphate DPP and its derivatives, and the benzoic acid derivative is terephthalic acid PTA and its esters.
5. The high-strength and low-warpage 3D printing nylon modified material according to claim 1, characterized in that: The maleic anhydride grafted toughening agent is at least one of maleic anhydride grafted polyethylene MAH-g-PE, maleic anhydride grafted polypropylene MAH-g-PP, maleic anhydride grafted polystyrene MAH-g-PS, maleic anhydride grafted polyethylene-vinyl alcohol copolymer MAH-g-EVOH, and maleic anhydride grafted thermoplastic elastomer MAH-g-TPE.
6. The high-strength and low-warping 3D printing nylon modified material according to claim 1, characterized in that: The conductive polymer is polyaniline.
7. The high-strength and low-warpage 3D printing nylon modified material according to claim 1, characterized in that: The layered dihydroxy compound Mg-Al LDH, the functionalized substance is a fluorine-containing polymer.
8. A method for preparing a high-strength, low-warpage 3D printing nylon modified material according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Drying the nylon resin: (2) adding the nylon resin, crystallization accelerator, maleic anhydride graft toughening agent, benzene ring-containing hyperbranched polymer, modified silicon carbide whisker, and modified carbon fiber obtained in step (1) into a high-speed mixer and mixing them evenly to obtain a mixture; (3) melt-blending, extruding and granulating the mixture obtained in step (2) using a twin-screw extruder to obtain granules; (4) The pellets obtained in step (3) are sent to a vacuum oven for drying, and then extruded through a single screw extruder, and then cooled in sections to obtain a 3D printing nylon modified material.
9. The method for preparing a high-strength, low-warpage 3D printing nylon modified material according to claim 8, characterized in that: The processing temperature of the twin-screw extruder in step (3) is 250-290°C.
10. The method for preparing a high-strength, low-warpage 3D printing nylon modified material according to claim 8, characterized in that: In step (4), the processing temperature of the single screw extruder is 250-290°C, and the cooling temperatures used in the segmented cooling process are set to 240°C, 220°C, 200°C, 180°C, 160°C, 100°C, and 40°C, respectively.
Citation Information
Cited By
Far infrared nanometer carbon fiber film and preparation method thereof
CN119967648A
